A legal study on the ratification of the 1951 un refugee convention in relation to the status of refugees and human trafficking in Malaysia / Nor Hazwani Zainal ...[et al.] - Zainal, Nor Hazwani; Idrus, Sakinah; Nazrin, Nabil; Kamarudin, Nur Azam (2009)
This report examines the problem of trafficking of women and children refugees in Malaysia, and whether the ratification of the 1951 Convention relating to the Status of Refugees (hereinafter "1951 Convention") could aid in the enforcement of the Anti-Trafficking in Persons Act 2007 (hereinafter "ATIP 2007") in addressing the problem. In analyzing the problem, the writers first delve into the historical and theoretical background of the 1951 Convention and the United Nations High Commissioners for Refugees. The report, then, proceeds to discuss the vital provisions within the 1951 Convention that discuss the rights of refugees especially women and children. Next, the report discusses the problem with the term "trafficking"; and furthermore gives a selected overview of the situation with regards the trafficking of women and children around the world. The report also discusses the Malaysian experience regarding its obligation towards refugees; and the ant trafficking law(s) that is in existence in the country precedent and succeeding the year 2007. In its conclusion, the report assimilates the issues of the flooding of refugees in Malaysia and their rights, as well as the trafficking of persons; and whether the ratification of the 1951 Convention is the answer to both problems. The report also addresses the sufficiency of the present Government's actions and laws in addressing the issue. The report recommends for non-ratification for various demographic, social and policies reasons; and for the Government to strengthen its enforcement of ATIP 2007 in helping protect the trafficked women and children refugees and in preventing further trafficking of these persons.